Concurrence of Acrodermatitis Enteropathica and Eczema Herpeticum in a Child with Atopic Dermatitis - Budi Satria; WenChieh Chen; Hardyanto Soebono; Sunardi Radiono; Retno Danarti (Karger Publishers, 2019)
Acrodermatitis enteropathica (AcE) is a rare, autosomal recessive inherited disorder caused by mutation of the SLC39A4 gene coding for zinc transport protein (ZIP 4). The disease appears during childhood especially in breastfeeding or post-breastfeeding infant. Eczema herpeticum refers to a disseminated skin infection of herpes simplex virus that usually leads to vesicular eruptions commonly seen on a background of atopic dermatitis (AD). We describe an 11-year-old boy with periorificial erosions in periorbital, perinasal, perioral, perineal, and gluteal areas, accompanied with itchy vesicles, some covered with hemorrhagic crusts. A clinical diagnosis of AcE and eczema herpeticum with AD was supported by typical lesions and acute and chronic eczematous changes found mainly in the flexural aspects of extremities, which is diagnostic of AD. Laboratory findings showed anti HSV1 IgG (23.43) and high levels of IgE (478.9 IU/L). There was no multinucleated giant cell in the Tzanck test. Skin histology was compatible with AcE. Direct immunofluorescent examination showed no deposits of IgG, IgM, IgA, or complement. Complete resolution occurred within 2 weeks of acyclovir and oral zinc supplementation.